PENGARUH PELATIHAN BUDIDAYA HIDROPONIK TOGA DAN PEMBUATAN PUPUK MOL TERHADAP PEMAHAMAN SERTA KEBERHASILAN BUDIDAYA TOGA OLEH IBU-IBU PERUMAHAN UNIVERSITAS TERBUKA - Dwisatyadini, Mutimanda; Kusumaningrum, Elizabeth Novi; Handayani, Sri Kurniati; Hewindati, Yuni Tri (Universitas Mataram, 2024)
ABSTRACT The provision that needs to be given to the mothers of Perum UT residents who are members of Majelis Taklim Darul Ulum is knowledge about family medicinal plants (TOGA) and how to cultivate them through hydroponic techniques. The hydroponic system began to be widely chosen because it has various advantages. These advantages include the cleaner products produced in this system. In addition, the nutrient solution given to plants is more measurable and always available. The Aim of this community service activity is to see the effect of training in hydroponic toga cultivation and making mole fertiliser on the understanding and success of TOGA cultivation of housewives. The method of implementing the activity begins with identifying the data needs of the Open University housing mothers and collecting data on the understanding and readiness of the mothers in participating in the training, providing counseling or training related to how to cultivate TOGA with hydroponics, as well as how to make mole fertiliser from stale rice and brown sugar. demonstrating how to cultivate TOGA with hydroponics (spinach, celery, cucumber, tomato), monitoring and evaluating the success of making TOGA hydroponic cultivation. The evaluation results of community service activities showed that knowing and understanding toga cultivation with hydroponics increased by 66%, which before the Toga cultivation training was 34% to 100%. Open University housing mothers have cultivated TOGA with hydroponics increased by 93%, which was previously 7% to 100%. Open University housing mothers are seen to know mole fertiliser from stale rice and brown sugar has increased after training by 80%, which was previously only 20% to 100%. Women's experience in making mole fertiliser from stale rice and brown sugar increased by 80% from the previous 20% to 100%. The mothers' understanding of how to make mole fertiliser from stale rice and brown sugar increased by 83% from 17% to 100%. And the results of mothers in demonstrating how to cultivate TOGA with Hydroponics are very good with an increase of 40% from the previous only 60% to 100%. In conclusion, the results of hydroponic vegetables are good, so that the dream of UT housing mothers to donate hydroponic vegetables around the Open University housing has been realised. Keywords: TOGA Cultivation Training, Hydroponics, Mole Fertiliser.